2019
DOI: 10.1002/ente.201900488
|View full text |Cite
|
Sign up to set email alerts
|

Aligned Electrospun Carbon Nanofibers as Electrodes for Vanadium Redox Flow Batteries

Abstract: Electrospun carbon nanofibers (CNFs) are regarded as potential electrode materials for vanadium redox flow batteries (VRFBs) due to the advantages of a large surface area and good electrochemical activity. However, woven CNFs with randomly distributed fibers are limited by poor permeability of the electrolyte, thus leading to a large mass‐transport polarization during battery operation. To address this issue, aligned carbon nanofiber (ACNF) webs are fabricated and applied in the battery with fibers parallel to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Additionally, it was found that the alignment delivered a sufficient anisotropy and obtained the highest permeability in the direction parallel to the aligned direction of the fibres, which added a new understanding to the effect of alignment to that of the elongated graphite planes and improved conductivity in the aligned direction demonstrated by Flox et al [115]. Alignment was also applied by Zhang et al [148] to address the low permeability issue in the direction of electrolyte flow and the aligned ECNF resulted in an increased limiting current density, 25% higher than that of carbon paper. For the widely applied ECNF/CF composite, the improved battery performance has also been ascribed to the variation of microstructure.…”
Section: Structure and Morphology Designmentioning
confidence: 93%
“…Additionally, it was found that the alignment delivered a sufficient anisotropy and obtained the highest permeability in the direction parallel to the aligned direction of the fibres, which added a new understanding to the effect of alignment to that of the elongated graphite planes and improved conductivity in the aligned direction demonstrated by Flox et al [115]. Alignment was also applied by Zhang et al [148] to address the low permeability issue in the direction of electrolyte flow and the aligned ECNF resulted in an increased limiting current density, 25% higher than that of carbon paper. For the widely applied ECNF/CF composite, the improved battery performance has also been ascribed to the variation of microstructure.…”
Section: Structure and Morphology Designmentioning
confidence: 93%
“…C-LB1500 retained more than 95.0% capacitance after 10 000 GCD tests at a current density of 10 A g –1 , compared to C-LB200 which retained 70.6% capacitance. The EIS tests (Figure ) suggested that although the orientation of the CFNs increased the resistance of the charge transport of the electrode (proportional to the diameter of the semicircles), probably owing to less intercontact of the fibers in the oriented CFNs, a more organized network structure should decrease the electrolyte ion diffusion resistance, ,, which made C-LB1500 capable of storing more energy and gave it a longer service life.…”
Section: Resultsmentioning
confidence: 99%
“…In parallel, Choi et al [38] additionally suggested that the regular ordering and alignment of TiO2 nanoparticles improved the photocatalytic performances. This effect can be attributed in part to enhanced transport in aligned nanostructures as suggested by several experimental [39,40] and modeling [41,42] works. Mesoporous fibers of other oxides like silica were also obtained with the EISA adapted approach [43,44].…”
Section: Introductionmentioning
confidence: 80%